Forced Migration from Karnali to the Lowlands: Maoist Insurgency-Driven Displacement in Nepal (2052–2062 BS) - Acharya, Bishweshwar Prasad (Academia Research Journal, 2026)
The Maoist insurgency in Nepal (2052–2062 BS) triggered widespread internal displacement, particularly from remote mountain districts in Karnali Province. This study examines large-scale forced migration from Jumla, Humla, and Mugu to safer lowland areas in Surkhet and Nepalgunj (Banke District), driven by intense violence in these underdeveloped regions. The decade-long conflict claimed over 17,000 lives and displaced an estimated 100,000–200,000 people nationwide, with Karnali's western hills severely affected due to geographic isolation, poverty, and disruptions to agriculture and services. Utilizing secondary data from Central Bureau of Statistics (CBS) censuses (2001 and 2011), OHCHR Nepal Conflict Report, and related studies, the analysis shows moderated population growth in origin districts; Jumla (89,427 to 108,921), Humla (40,595 to 50,858), Mugu (43,937 to 55,286); contrasting sharp increases in destinations: Surkhet (288,527 to 350,804) and Banke (approximately 385,840 to 491,313). Qualitative evidence from reports highlights conflict as a key push factor, including threats, forced recruitment, extortion, and insecurity, compounded by economic vulnerabilities. Many displaced from Karnali districts sought refuge in urban hubs like Nepalgunj and Surkhet for security and opportunities, with residual IDPs (around 50,000 in 2015) often in Terai regions. The findings reveal how insurgency exacerbated structural inequalities, accelerating highland-to-lowland shifts and contributing to urban influxes and rural depopulation. This research elucidates conflict's role in reshaping Nepal's internal migration patterns, informing post-conflict policies for rehabilitation and balanced demographic development in vulnerable provinces like Karnali.